Canonical Versus Non-Canonical Passives in Indonesian - Udayana, I Nyoman; Aryawibawa, I Nyoman; Madia, I Made (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
While many studies have explored passive constructions in Indonesian, there is still a significant gap in research focusing on distinguishing passive clauses and categorizing them into canonical and non-canonical forms. This study aims to address this gap by identifying different types of passive clauses in Indonesian and classifying them into these two categories. The primary objectives are to establish clear criteria for validating the existence of canonical and non-canonical passive forms and to provide evidence supporting their distinction. To achieve these aims, we first analyze markers on Indonesian verbs, particularly the prefixes di-, ter-, and unmarked (zero) forms. The data used for this analysis consists of naturally occurring expressions and clauses sourced from the Leipzig Corpora. This data is examined through the lens of the (non)-canonical theory of passivization. The findings indicate that the di- marker on verbs predominantly signals canonical passive constructions. However, there are cases where the di- form shifts to non-canonical usage, especially when the agent is obligatorily present and cannot be syntactically demoted to an oblique role. In contrast, the ter- form and the unmarked form, which can denote either a bare active (BA) or a bare passive (BP) construction, consistently represent non-canonical passive constructions.